Learning jQuery 3 : build interesting, interactive sites using jQuery by automating common tasks and simplifying the complicated ones - Boduch, Adam; Chaffer, Jonathan; Swedberg, Karl, 1967- (Packt Publishing, 2017)
Create efficient and smart web applications with jQuery 3.0 using this step-by-step practical tutorial About This Book Create a fully featured and responsive client-side application using jQuery Explore all the latest features of jQuery 3.0 and code examples updated to reflect modern JavaScript environments Develop high performance interactive pages Who This Book Is For This book is ideal for client-side JavaScript developers. You do need to have any previous experience with jQuery, although basic JavaScript programming knowledge is necessary. What You Will Learn Create custom interactive elements for your web designs Find out how to create the best user interface for your web applications Use selectors in a variety of ways to get anything you want from a page when you need it Master events to bring your web pages to life Add flair to your actions with a variety of different animation effects Discover the latest features available in jQuery with the latest update of this incredibly popular title Using jQuery npm Packages In Detail If you are a web developer and want to create web applications that look good, are efficient, have rich user interfaces, and integrate seamlessly with any backend using AJAX, then this book is the ideal match for you. We'll show you how you can integrate jQuery 3.0 into your web pages, avoid complex JavaScript code, create brilliant animation effects for your web applications, and create a flawless app. We start by configuring and customising the jQuery environment, and getting hands-on with DOM manipulation. Next, we'll explore event handling advanced animations, creating optimised user interfaces, and building useful third-party plugins. Also, we'll learn how to integrate jQuery with your favourite back-end framework. Moving on, we'll learn how the ECMAScript 6 features affect your web development process with jQuery. we'll discover how to use the newly introduced JavaScript promises and the new animation API in jQuery 3.0 in great detail, along with sample code and examples. By the end of the book, you will be able to successfully create a fully featured and efficient single page web application and leverage all the new features of jQuery 3.0 effectively. Style and approach Create efficient client-side apps that look great and run seamlessly across all devices with this step-by-step practical guide. There are illustrative examples for those who need extra help to get started with jQuery web development.